Regulation of GLUT4 translocation in an in vitro cell model using postprandial human serum ex vivo. Issue 6 (29th March 2019) - Cogan, Karl E.; Carson, Brian P.; Patel, Bijal; Amigo‐Benavent, Miryam; Jakeman, Philip M.; Egan, Brendan
Abstract : New Findings: What is the research question? This study used a new experimental model, in which culture medium is conditioned with human serum ex vivo, to investigate nutrient‐mediated regulation of GLUT4 translocation in skeletal muscle cells in vitro . What is the main finding and importance? Human serum stimulated GLUT4 translocation, an effect differentially modulated by whether the culture medium was conditioned with serum from fasted subjects or with serum collected after feeding of intact or hydrolysed whey protein. Conditioning cell culture medium with human serum ex vivo represents a new approach to elucidate the effects of ingesting specific nutrients on skeletal muscle cell metabolism. Abstract: Individual amino acids, amino acid mixtures and protein hydrolysates stimulate glucose uptake in many experimental models. To replicate better in vitro the dynamic postprandial response to feeding in vivo, in the present study we investigated the effects of culture media conditioned with fasted and postprandial human serum on GLUT4 translocation in L6‐GLUT4 myc myotubes. Serum samples were collected from healthy male participants ( n  = 8) at baseline (T0), 60 (T60) and 120 min (T120) after the ingestion of 0.33 g (kg body mass) −1 of intact (WPC) or hydrolysed (WPH) whey protein and an isonitrogenous non‐essential amino acid (NEAA) control. L6‐GLUT4 myc myotubes were starved of serum and amino acids for 1 h before incubation for 1 h in medium containing 1% postprandial human serum, after which GLUT4 translocation was determined via colorimetric assay. Medium conditioned with fasted human serum at concentrations of 5–20% increased cell surface GLUT4 myc abundance. Incubation with serum collected after the ingestion of WPH increased cell surface GLUT4 myc at T60 relative to T0 [mean (lower, upper 95% confidence interval)]; [1.13 (1.05, 1.22)], whereas WPC [0.98 (0.90, 1.07)] or NEAA [1.02 (0.94, 1.11)] did not. The differential increases in cell surface GLUT4 myc abundance were not explained by differences in serum concentrations of total, essential and branched‐chain amino acids or insulin, glucagon‐like peptide 1 (GLP‐1) and gastric inhibitory polypeptide (GIP). Using a new ex vivo, in vitro approach, cell culture medium conditioned with postprandial serum after the ingestion of a whey protein hydrolysate increased GLUT4 translocation in skeletal muscle cells. Abstract :